1985
DOI: 10.1016/0048-3575(85)90093-8
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic microsomal oxidative metabolism of pesticides and other xenobiotics in pregnant CD1 mice

Abstract: Pregnancy-related changes in oxidative metabolism of several xenobiotics including pesticides were examined in the hepatic microsomes of CD, mice. The effect of pregnancy on hepatic microsomal cytochrome P-450~catalyzed substrate oxidation was found to be dependent upon the type of reaction examined. Not all substrates undergoing the same reaction showed identical changes during pregnancy. Those enzyme activities which exhibited a decline in specific activity during pregnancy generally exhibited no change in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Organophosphates are bioactivated by desulfuration of the phosphorothionate sulfur to produce the oxon, a metabolite that is orders of magnitude more potent in cholinesterase inhibition (Neal & Halpert, 1982;Jokanovic, 2001). FMO-dependent oxidation of the thioether moiety produces the sulfoxide, a pathway that represents detoxication compared to oxon production (Hajjar & Hodgson, 1980Kulkarni & Hodgson, 1984;Osimitz & Kulkarni, 1985;Tynes & Hodgson, 1985b;Kinsler et al, 1988Kinsler et al, , 1990Buronfosse et al, 1995;Hodgson et al, 1998;Usmani et al, 2004). Again, we have found human FMO2 to be very effective at S-oxygenation of the thioether of phorate and disulfoton (Henderson et al, 2004a), as has been previously shown for other FMO enzymes and for the mouse FMO2 (Karoly & Rose, 2001).…”
Section: Genetic Polymorphisms Of Flavin-containing Monooxygenasementioning
confidence: 99%
“…Organophosphates are bioactivated by desulfuration of the phosphorothionate sulfur to produce the oxon, a metabolite that is orders of magnitude more potent in cholinesterase inhibition (Neal & Halpert, 1982;Jokanovic, 2001). FMO-dependent oxidation of the thioether moiety produces the sulfoxide, a pathway that represents detoxication compared to oxon production (Hajjar & Hodgson, 1980Kulkarni & Hodgson, 1984;Osimitz & Kulkarni, 1985;Tynes & Hodgson, 1985b;Kinsler et al, 1988Kinsler et al, , 1990Buronfosse et al, 1995;Hodgson et al, 1998;Usmani et al, 2004). Again, we have found human FMO2 to be very effective at S-oxygenation of the thioether of phorate and disulfoton (Henderson et al, 2004a), as has been previously shown for other FMO enzymes and for the mouse FMO2 (Karoly & Rose, 2001).…”
Section: Genetic Polymorphisms Of Flavin-containing Monooxygenasementioning
confidence: 99%